Determination of Polycyclic Aromatic Hydrocarbons in Textiles by Gas Chromatography-Mass Spectrometry. Issue 6 (November 2016) - Li, Xueyang; Yang, Yongchao; Yang, Xue; Li, Jing; Li, Shufen; Tang, Shaokun
A sensitive and fast method using gas chromatography-mass spectrometry (GC-MS) analysis was developed for simultaneous determination of 16 polycyclic aromatic hydrocarbons (PAHs) in functional textile samples. The method under optimized conditions exhibited good linearity with linear correlation coefficients between 0.9930 and 0.9999, with maximum recoveries within 74.0∼99.0%, and with relative standard deviation (RSD) of 0.89 to 4.94%. Quantitation and detection limits ranged from 1.3 to 12.2 üg/L and 0.4 to 3.8 üg/L, respectively. These values were less than the limits of two relative standards (Oeko-Tex Standard 100 and ZEK 01.2-08). When applied to coated denim fabric and waterproof tarpaulins, results showed that PAH concentrations in waterproof tarpaulins were greater than the limits of the two relative standards.